Regional Government Cooperation in Keeping Brantas River Basin with Sumber Brantas Village Community, Bumiaji Sub-District, Batu City - Hodaifah, N; Masduki, M.; Sulistyangingsih, Tri (Government Studies of Muhammadiyah Malang University/AIPPTM, 2018)
Awareness of Batu City residents to keep the Brantas River is still low, whereas Batu Regional Government has Regional Regulation (PERDA) No. 7 of 2011 on Spatial Planning for Year 2010-2030 and Regional Regulation No 16 Year 2011 on Protection, Conservation and Environmental Management. From the existing regulations should be enough to help the existence of forests that support the Brantas watershed, but the systematization of natural resource management is still not communicated well by the surrounding community. Lack of understanding and awareness in cooperation is a gap that makes the goal in protecting and preserving the Brantas River Basin did not materialize. The importance of growing mutual attitude among the community is needed to control the problems that occur in the Brantas River Basin. This raises the question for the researcher as stated in the formulation of the problem in this research, that is (1) How Local Government Action in effort to tackle Brantas Watershed? (2) How is the cooperation between the Regional Government and SumberBrantas Village Communities in maintaining the Brantas River? (3) How is the social life of SumberBrantas Village community in maintaining the Brantaswatershed?The type of research is descriptive qualitative research (Description Research). The research area was chosen purposively, in SumberBrantas Village, Bumiaji District, Batu City. This study uses field notes and in-depth interviews of informants namely the Local Government and the Brantas River Basin community. The data obtained will be analyzed using qualitative descriptive technique and the data is checked for validity by triangulation. The findings of the research results, the cooperation between the Government and the SumberBrantas Village Communities are still not optimal, because the community participation is still weak, this makes the problems that occur in the Brantas watershed protracted in handling. The village community of SumberBrantas is categorized as a farmer community which is known to still be thick with work together, it can be seen in the daily life of the community as well as the capital to increase people's understanding of the importance of keeping the Brantas watershed together.